PORTFOLIO ASSESSMENT FOR AN UNDERGRADUATE INTERMEDIATE LEVEL WRITING CLASS - Pakasi, Jenny H.; Beal, Jeremy (Universitas Pendidikan Indonesia, 2018)
Portfolio assessment has long been advocated as a means for students to reflect on and improve their writing. It allows students and teachers to identify consistent areas of strength and weakness to improve the students’ writing. This paper reports on an action research study in a third semester writing class in the English department of Sam Ratulangi University in Indonesia. The objective is to determine how and to what extent portfolio assessment is useful for improving students’ writing. Each student kept a portfolio of their written work, which was used by the teachers to analyze students’ progress over the course of the semester. Students wrote several paragraphs, with each paragraph going through three drafts and incorporating self- and peer-editing, in addition to being edited by a course instructor. At the end of the semester, the teachers compared the students’ writing from the beginning, middle, and end of the semester. Their writing was analyzed to determine changes in paragraph development, organization, and selected grammatical features. In general, the development and organization of the students’ writing showed significant improvement, while results for grammar were less consistent, depending more on individual factors and error type.